Chinese herbal medicine for the treatment of small intestinal bacterial overgrowth (SIBO): A protocol for systematic review and meta-analysis - Ren, Xuetong; Di, Zirui; Zhang, Zhe; Fu, Bingqian; Wang, Yuman; Huang, Chongxin; Du, Yanru (Medicine (Baltimore), 2020)
Chinese medicine has a unique theory and the Chinese herbal medicine treatment is based on the integral concepts and syndrome differentiation of the Traditional Chinese Medicine system. Although antibiotics remain the mainstay of SIBO treatment, various alternative or adjunctive therapies are available, including prokinetic agents, dietary interventions, probiotics, and herbal combinations. There is accumulating evidence demonstrating the antimicrobial properties of a growing number of herbs including garlic, black cumin, cloves, cinnamon, thyme, all-spices, bay leaves, mustard, and rosemary. This has prompted an interest in herbal therapy for the treatment of SIBO. Currently, there is no systematic review focusing on efficacy of CHM in the treatment of SIBO with PCOS, so our meta-analysis aims to comprehensively explore it. Meanwhile we will provide high-quality evidence to help patients, clinicians as well as health policymakers select better treatment strategy of PCOS. We will search the following sources without restrictions for date, language, or publication status: PubMed, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL) Cochrane Library, EMBASE and China National Knowledge Infrastructure. We will apply a combination of Medical Subject Heading (MeSH) and free-text terms incorporating database-specific controlled vocabularies and text words to implement search strategies. We will also search the ongoing trials registered in the World Health Organization's International Clinical Trials Registry Platform. Besides, the previous relevant reviews conducted on CHM for SIBO and reference lists of included studies will also be searched. This study will provide a reliable basis for the treatment of SIBO with CHM. The findings will be an available reference to evaluate the efficacy and safety of CHM in the treatment of SIBO. INPLASY202080004.